Interoperabilitas antar matra dalam skema perang berlarut - M Nakir; Arief Prayitno; Ridwan Gunawan (JRTI (Jurnal Riset Tindakan Indonesia), 2023)
The discourse on the development of the military strategy nowdays is inseparable from the globalization. Defense experts are faced with an increasing trend of international system instability and it is increasingly difficult to predict. The presence of new technology also influences the characteristics of modern conflicts where future wars are becoming increasingly complex. In general, wars are planned by the aggressor for a short period of time in order to achieve victory quickly, however, the little ones force long-lasting wars as protracted wars. This study uses a qualitative method with a descriptive design. The purpose of this study is to analyze how far the interopability between the branches of the land arm in the protracted war scheme in Indonesia is. The research was carried out at the Army Headquarters and the Army Education and Training Command. The research data were analyzed in four steps, namely data reduction, presenting data, integrating data and drawing conclusions. The results of the study indicate that it requires strengthening of interopability between dimensions in the protracted war scheme in Indonesia. The conclusion is that in modern warfare, interoperability is absolutely necessary in military operations. Suggestions for the need for further research on interoperability between branches in the Army Forces in a protracted war scheme are more specific in one large island defense area.